Pulmonary rehabilitation in exacerbations of chronic obstructive pulmonary disease: a person-centred research - Machado, Ana Filipa Marques Rego (2024)
Symptoms, functional status and exacerbations are key problems in people with chronic obstructive pulmonary disease (COPD) and strong contributors to the disease burden; nevertheless, these problems are still not fully understood. Thus, understanding symptoms, functional status and the course of exacerbations of COPD (ECOPD), and identifying strategies to minimise their burden are recognised research priorities. This thesis aimed to i) understand symptoms and functional status in people with COPD, ii) establish the impact of ECOPD from a clinical and patient point of view, and iii) explore how pulmonary rehabilitation (PR) can counteract these problems. A narrative review (Chapter 2), a cross-sectional study (Chapter 3) and a secondary analysis of this study (Chapter 4), a scoping review (Chapter 5), a qualitative study (Chapter 6), a systematic review (Chapter 7) and a randomised controlled trial (Chapter 8) were conducted. Chapters 2, 3 and 4 addressed aim i), Chapters 5 and 6 addressed aim ii), and Chapters 2, 6, 7 and 8 addressed aim iii). Chapter 2 showed the high prevalence of respiratory and non-respiratory symptoms, their underlying mechanisms and impact in the daily life of people with COPD, and the role of interdisciplinary PR in effective tackling these symptoms complexity. Chapter 3 found that people with COPD, from all levels of disease severity, have decreased functional status and that this impairment cannot be accurately reflected through other patient-reported or clinical outcomes. Chapter 4 showed how the use of different criteria impact the classification of functional impairment and identified the most consistent methods to determine functional impairment in people with COPD. Chapter 5 showed that ECOPD result in an acute worsening of symptoms and impact of the disease and a decrease in functional status, which are sustained on a long-term and contribute to a decline in quality of life. Chapter 6 found that outpatient-managed ECOPD have a huge negative impact on people’s lives, which is reflected on symptoms, physiological changes, limitations in activities of daily living, social constrains, psychological and emotional challenges, and family disturbances. Chapter 7 showed that PR is safe in people with ECOPD and that programmes for this population should be composed by exercise training, breathing techniques and education and psychosocial support. Lastly, Chapter 8 found that a 3-weeks home-based PR programme in people with outpatient-managed ECOPD is safe, more effective than just pharmacological treatment, and results in positive short-term effects and self-perceived impact on symptoms, physical activity, activities of daily living, functional capacity and health status. This thesis provides important information on the comprehensive assessment and management (through PR) of people with COPD, particularly during ECOPD, and supports the implementation of PR programmes for (outpatientmanaged) ECOPD. This new knowledge can be used to guide future interventions, guidelines and political decisions to increase awareness and access to PR for all people with ECOPD.